Leveraging 3D Printing Technology to Facilitate Quranic Education for the Visually Impaired - Ts. Dr. Hatika Kaco; Khairina Iqlima Batrisyia Khairil Anuar; Nurinsyirah Najihah Izharruzzahir; Izzminhal Akmal Norhisyam; Muhammad Amir Rafiq Rahmat; Mohd Shaiful Sajab; Fadzidah Mohd Idris (Universiti Sains Islam Malaysia, 2025)
Indexed by MyCite